Comparison of national strategies in France, Germany and Switzerland for DRR and cross-border crisis management. (2018) - Abad, J.; Booth, L.; Marx, S.; Ettinger, S.; Gérard, F.
Abstract: The ESPREssO project (funded by the European Union's Horizon 2020 research and innovation programme, under Grant Agreement No. 700342) prioritises the need for overcoming barriers to disaster risk reduction (DRR) in Europe, with cross-border crisis management identified as one of its three central challenges. In this paper, we present a synthesis of the different legal, policy and scientific approaches to DRR in France, Germany and Switzerland, through work carried out for the ESPREssO project on the basis of stakeholder interviews and an analysis of legal and policy references. A comparison of these three differing DRR strategies is then carried out, focusing specifically on resulting impacts for cross-border crisis management, capitalizing on lessons learned from the tri-national border region Upper Rhine Valley to complete the analysis.